On the progress in flexibility and grid charges in light of the energy transition: The case of Germany. (June 2022) - Hanny, Lisa; Wagner, Jonathan; Buhl, Hans Ulrich; Heffron, Raphael; Körner, Marc-Fabian; Schöpf, Michael; Weibelzahl, Martin
Abstract: In the course of the energy transition, flexibility on the demand side is crucial to balance intermittent supply from renewable energy sources. In Germany, however, a large part of the demand side flexibility potential remains unused, especially due to an outdated and inappropriate grid charges regulation. In this respect, policymakers have failed to align their regulatory instruments, e.g., grid charges, to the flexibility requirements of the energy transition. Moreover, regulatory and planning uncertainties regarding the long-term vision for future electricity systems inhibit flexibility investments – marking another policy failure. Although the above issues are known to policymakers for quite some time, too little has been done to further develop corresponding regulation. This policy inaction results from a decision-making dilemma, in which policymakers did not reach a solution that benefits all stakeholders involved in the grid charges debate (e.g., energy-intensive and less energy-intensive electricity consumers). Solving the policy failure in the form of a revised and future-proof grid charges regulation will, however, increase the prospect of a just outcome for society and, more specifically, recognition and cosmopolitan justice. In this paper, we outline how grid charges inhibit demand side flexibility in Germany and which policy failures have ultimately contributed to stuck political decision-making. We further provide concrete suggestions of how existing policy failures may be corrected in order to ensure a successful energy transition as a policy guide for Germany and other countries all around the world. Highlights: German grid charges inhibit the provision of demand side flexibility. Opening regulation for demand side flexibility is crucial for the energy transition. Also, future grid charges need to provide transparency and legal certainty. Well-designed grid charges contribute to a just and sustainable energy transition. Future grid charges regulation may serve as a blueprint for countries worldwide.